UJI KINERJA PENGOLAHAN AIR SIAP MINUM DENGAN PROSES BIOFILTRASI, ULTRAFILTRASI DAN REVERSE OSMOSIS (RO) DENGAN AIR BAKU AIR SUNGAI - Said, Nusa Idaman (Jurnal Air Indonesia, 2009)
Water is a very basic need for humans, especially for cooking and drinking. With the rapid growth of population in particular need of clean water for the community also increased in numbers. The problem is with the poor quality of raw water for drinking water, then in addition to expanding its production costs, the result is often less good. One of the problems or issues that are often found in drinking water in the world these days that is the emergence of compounds called Trihalomethanes or THMs abbreviated, as a side effect of the disinfection process with a chlorine gas or hypochlorite compounds.Currently, to removal organic pollutants, ammonia, detergents, odor and other micro pollutants in drinking water, PAM is usually used by the process of manufacturing processes using adsorbsi Powder Active Carbon Adsorption, continued with physicals processing is the process of coagulation, flocculation, sedimentation and disinfection with chlorine. With increasingly high prices of powdered activated carbon, coagulant and flocculant chemicals, then the cost of treating drinking water to be increasing. To solve the problem above, one alternative is to develop clean water treatment technologies using a combination of biofiltration and ultrafiltration process, and to produce drinking water to proceed with processing using the process of reverse osmosis. Within the combination of biofiltration, ultrafiltration and reverse osmosis processes to treat the river water can be produced the drinking water with a very good quality without the use of chemicals for coagulation-flocculation process, and operational costs are relatively low.Ã‚Â Key words : Air siap minum, biofiltrasi, ultrafiltrasi, reverse osmosis